1995
DOI: 10.1016/0304-3959(94)00171-a
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord stimulation in animal models of mononeuropathy: effects on the withdrawal response and the flexor reflex

Abstract: Spinal cord stimulation (SCS) is efficacious for pain due to injury of peripheral nerves, and therefore models of mononeuropathy appear to be particularly suitable for an experimental approach to the study of mechanisms underlying the clinical effect of this mode of treatment in chronic neuropathic pain. Virtually all previous experimental studies on SCS have utilized acute and nociceptive types of peripheral pain stimuli to explore the attenuating effects of SCS. In the present study we made use of the two mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(83 citation statements)
references
References 40 publications
1
76
0
6
Order By: Relevance
“…This notion is further supported by the finding that the threshold of the early component of the flexor reflex, which is Ab-fiber mediated, is elevated whereas the late C-fiber-dependent phase was found to be unaffected. 22 However, it has also been reported that the C-fiber flexor reflex can be significantly attenuated, but this observation was made in normal, intact animals. 23 Recently, the effect of SCS on long-term potentiation (LTP) has been investigated.…”
Section: Neurophysiological Mechanisms Studied In Animal Models Of Nementioning
confidence: 90%
“…This notion is further supported by the finding that the threshold of the early component of the flexor reflex, which is Ab-fiber mediated, is elevated whereas the late C-fiber-dependent phase was found to be unaffected. 22 However, it has also been reported that the C-fiber flexor reflex can be significantly attenuated, but this observation was made in normal, intact animals. 23 Recently, the effect of SCS on long-term potentiation (LTP) has been investigated.…”
Section: Neurophysiological Mechanisms Studied In Animal Models Of Nementioning
confidence: 90%
“…The maximal amplitude (baseline to peak) and latency to onset of the evoked MUAPs were measured for the first and second components of the response. 26 The first component appears after low-intensity stimuli that excite ␤-amyloid (A␤) afferent fibers as a short-lasting biphasic or triphasic deflection, whereas the second component is elicited by excitation of A␦ afferent fibers at higher stimulus intensity and consists in a longer-lasting volley of MUAPs.…”
Section: Functional Evaluationmentioning
confidence: 99%
“…Spinal cord stimulation induced an increase of these abnormally lowered withdrawal thresholds, which are mediated through alpha and beta fibers. These observations suggests SCS predominantly affects pain related to abnormal A fiber function, as in allodynia ( Handwerker et al, 1975;Carstens & Campbell, 1988;Garcia-Larrea et al, 1989;Meyerson et al, 1995;Oakley & Prager, 2002). Repetitive noxious stimulation of primary afferent fibers after peripheral nerve injury induces long-term changes of the excitability of spinal cord neurons (Rygh et al, 1999).…”
Section: Neurophysiological Mechanismsmentioning
confidence: 98%